All-solid-state lithium battery high-nickel positive electrode material, preparation method and all-solid-state lithium battery

By constructing a protective layer with a gradient cation disorder structure on the surface of single-crystal LiNi0.92Co0.06Mn0.02O2, the problem of structural degradation of ultra-high nickel cathode materials under high voltage was solved, and high cycle stability and high specific capacity of all-solid-state batteries were achieved.

CN120895608APending Publication Date: 2025-11-04NANJING UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510869870.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-25
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Existing ultra-high nickel cathode materials are prone to react with solid electrolytes under high voltage, leading to structural degradation, severe Ni2+/Li+ mixing, and easy oxidation of lattice oxygen to form oxygen loss, which affects the cycle stability and energy density of all-solid-state batteries.

Method used

A protective layer with a gradient cation disorder structure was constructed on the surface of single-crystal LiNi0.92Co0.06Mn0.02O2. An approximately 3 nm thick rock salt phase structure was formed by Al and B doping to suppress the reaction of Ni4+ with the electrolyte and enhance the lattice oxygen stability.

Benefits of technology

It effectively reduces Ni2+/Li+ mixing, improves interface stability, enhances the cycling performance and conductivity of materials under high voltage, extends battery life, and maintains high specific capacity and coulombic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120895608A_ABST
    Figure CN120895608A_ABST
Patent Text Reader

Abstract

The invention relates to an all-solid-state lithium battery high-nickel positive electrode material, a preparation method and an all-solid-state lithium battery, and belongs to the technical field of lithium batteries. Aiming at the interface problem of a high-nickel oxide positive electrode material and a chloride solid electrolyte, Al and B are creatively used for constructing a gradient cation disordered structure protection layer on a near surface, and a controllable structure gradient from a disordered structure to an ordered structure is formed when the surface is transited to a bulk phase; on one hand, a surface cation disordered structure can avoid direct contact between a solid electrolyte and high-oxidability Ni < 4 + > to further inhibit interface side reaction, and on the other hand, doping of an Al element on a near surface can improve stability of lattice oxygen, formation of oxygen under high cut-off voltage can be reduced, and stability of the structure is improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to a full-solid-state lithium battery high-nickel positive electrode material, a preparation method and a full-solid-state lithium battery, and belongs to the technical field of lithium batteries. BACKGROUND

[0002] The full-solid-state lithium battery based on inorganic solid-state electrolytes is considered as a frontier technology of a new generation of electrochemical energy storage systems due to its high energy density and safety advantages. Current research focuses on developing solid-state electrolytes with ultra-high ionic conductivity and excellent electrode / electrolyte chemical / electrochemical compatibility. Although oxide and sulfide solid-state electrolytes are highly concerned, their inherent defects still restrict practical application. The oxide system is limited by the low ionic conductivity of the electrolyte and poor solid-solid interface physical contact; the sulfide system is difficult to achieve the synergistic improvement of energy / power density and cycle life due to poor compatibility with high-voltage positive electrode materials. In recent years, chloride solid-state electrolytes represented by Li3InCl6, Li3YCl6, LiNbOCl4 and LiTaOCl4 have attracted much attention due to their ultra-high ionic conductivity (1-10 mScm -1 ) and high oxidation resistance potential (4.3 V) and excellent mechanical ductility, realizing the balance of conductivity and electrochemical stability that the oxide and sulfide systems cannot achieve. Experiments show that when the chloride solid-state electrolyte is matched with LiCoO2 and high-nickel positive electrode, it exhibits low interface impedance, high coulomb efficiency and excellent cycle stability, highlighting its application potential in high-performance full-solid-state batteries. At present, the full-solid-state battery based on NCM811 chloride electrolyte has realized cycle stability under high surface capacity at a 4.3 V cutoff voltage; to further improve the energy density of the full-solid-state battery, a low-cost ultra-high nickel (nickel content > 90%) positive electrode is used to increase the cutoff voltage to obtain higher specific capacity. The ultra-high nickel positive electrode can provide a specific capacity of >220 mAhg -1 , excellent rate performance and low cost advantage. However, for the ultra-high nickel positive electrode, especially under high-voltage cutoff, it will suffer from serious interface problems. On the one hand, the high oxidizing Ni 4+ is easy to react with the solid-state electrolyte, causing the degradation of the structure of the electrode material; on the other hand, the lattice oxygen of the positive electrode itself will be oxidized into superoxygen under high-voltage cutoff conditions, which is easy to form oxygen loss; all of these will cause the structure degradation and rapid capacity decline of the Ni 2+ / Li + cations in the ultra-high nickel. However, the methods such as doping or simple concentration gradient design cannot meet the requirements of high-voltage operation for stabilizing the cycle performance under high delithiation rate, because these post-modifications cannot change the intrinsic properties of the structure, which is the main bottleneck restricting the improvement of these strategies. SUMMARY

[0003] The application is directed to a single crystal LiNi 0.92Co 0.06 Mn 0.02 O2 and chloride solid-state electrolyte interface problems, the protective layer of gradient cationic disordered structure is constructed near the surface by using Al and B innovatively, which has a controllable structure gradient from disordered structure to ordered structure when the surface transitions to the bulk phase, on the one hand, the surface cationic disordered structure can avoid direct contact between the solid-state electrolyte and the high-oxidizing Ni4+, thereby inhibiting the interface side reaction, on the other hand, the doping of Al element near the surface can improve the stability of lattice oxygen, which can reduce the formation of oxygen at high cutoff voltage and improve the stability of the structure.

[0004] A full-solid-state lithium battery high-nickel positive electrode material, comprising a high-nickel oxide bulk phase, the bulk phase is a single crystal particle, and an Al and B containing coating layer is further included on the surface of the bulk phase, the thickness of the coating layer is 1-10 nm, and Al elements are distributed in the range of 1-10 nm near the outer surface of the bulk phase, the content of Al elements gradually decreases from the near surface to the bulk phase, and the coating layer changes from cationic disordered arrangement to cationic ordered arrangement from the outside to the inside.

[0005] The particle size of the single crystal particle is 1-20 μm.

[0006] The preparation method of the above positive electrode material comprises the following steps:

[0007] A high-nickel precursor material is obtained, which is mixed with a lithium source by ball milling and then subjected to a first calcination;

[0008] The pre-fired material is fully mixed with B2O3 and Al2O3, and then subjected to a second calcination to obtain the positive electrode material.

[0009] The high-nickel precursor material is Ni 0.92 Co 0.06 Mn 0.02 (OH)2.

[0010] The first calcination is pre-fired at 450-550℃ for 4-10h, and then heated to 700-800℃ for 15-25h; the second calcination is at 800-850℃ for 15-25h.

[0011] The amount of B2O3 and Al2O3 is 1-10 mol% of the pre-fired material.

[0012] The lithium source is LiOH H2O and LiNO3, and the molar ratio is 1:0.5-2; the molar amount of lithium source is 1.5-2.5 times the molar amount of precursor.

[0013] A full-solid-state lithium battery comprising a positive electrode composed of the above positive electrode material.

[0014] A method for reducing the Ni 2+ / Li + mixing ratio on the positive electrode material of an all-solid-state lithium battery during charge-discharge cycling, which refers to forming the above-mentioned all-solid-state lithium battery high-nickel positive electrode material by coating a coating layer containing Al and B on the surface of a high-nickel oxide body phase.

[0015] The beneficial effects of the present application are: using Al and B to construct a surface gradient cation disorder structure protective layer of about 3nm on the surface of single crystal LiNi 0.92 Co 0.06 Mn 0.02 O2, the outermost side is a rock salt phase structure, the inside is a layered structure, and the middle is a mixed structure, which is a gradient cation disorder structure; the interface layer can effectively reduce the side reaction between high-activity high-valence nickel and solid-state electrolyte, and reduce the Ni 2+ / Li + cation mixing and ensure the stability of the layered structure. After interface aging test, the interface impedance is only 175Ω, while the interface impedance of the control sample is as high as 1500Ω. At the same time, the charge transfer resistance is also reduced from 110Ω to 40Ω at the first full charge state, and the disorder structure protective layer effectively ensures the ion transmission of the interface. Al doping near the surface can inhibit the release of lattice oxygen and maintain the stability of the layered structure, and the oxygen vacancy formation energy is increased from 0.3eV to 0.6eV at high voltage, which significantly improves the stability of lattice oxygen. In addition, the band gap is reduced from 0.42eV to 0.27eV due to the doping of Al, which improves the electronic conductivity of the material and improves the kinetics of the material. Benefiting from this cation disorder structure protective layer, the SNCM-BA positive electrode has a first cycle discharge specific capacity of 236.0mAhg -1 at 60℃ under 4.5V high voltage cut-off condition at 1C, and the first cycle coulombic efficiency is 91%, and the capacity retention rate is 86% after 200 cycles. In addition, at room temperature and a current density of 5C, the capacity retention rate is 94% after 500 cycles. BRIEF DESCRIPTION OF DRAWINGS

[0016] Figure 1 : (a) XRD patterns of SNCM-Bare and (b) SNCM-BA, (c) SEM images of SNCM-Bare and (d) SNCM-BA.

[0017] Figure 2 : (a) HADDF image of SNCM-BA, and the corresponding (b) Ni element, (c) Al element, (d) B element, (e) O element, (f) O and Ni element mixture, (g) Al and Ni element mixture, (h) B and Ni element mixture image.

[0018] Figure 3: (a) B, Al, and Ni element line scan maps, (b) Al and B element EELS maps of SNCM-BA near surface

[0019] Figure 4 : (a) SNCM-BA atom HAADF-STEM image, (b) outermost region, (c) middle region, (d) inner region zoom-in image.

[0020] Figure 5 : (a) Full solid-state battery electrochemical performance at 1C current density 60 °C, (b) corresponding first cycle charge-discharge curves.

[0021] Figure 6 : (a) SNCM-BA and (b) SNCM-Bare corresponding dQ / dV curves at different cycles at 1C -1

[0022] Figure 7 : SNCM-BA and SNCM-Bare full solid-state battery cycle stability curves at 5C.

[0023] Figure 8 : (a) SNCM-BA and (b) SNCM-Bare in-situ interfacial aging test, corresponding (c) SNCM-BA and (d) SNCM-Bare EIS curves.

[0024] Figure 9 : (a) SNCM-BA and (b) SNCM-Bare DRT two-dimensional intensity color maps and charge-discharge curves.

[0025] Figure 10 : In-situ DEMS test (a) SNCM-Bare and (b) SNCM-BA gas evolution of O2 and CO2 during the first charging process DETAILED DESCRIPTION

[0026] Example 1

[0027] LiNi 0.92 Co 0.06 Mn 0.02 O2 single crystal preparation: Ni 0.92 Co 0.06 Mn 0.02 (OH)2 precursor powder was selected as raw material. Then, the precursor was mixed with LiOH H2O (5 mol% excess) and LiNO3 (LiOH H2O and LiNO3 molar ratio 1:1) uniformly by ball milling method, and then pre-sintered at 500 °C for 6 h under oxygen environment, and then heated to 820 °C for 18 h to obtain single crystal LiNi 0.92 Co 0.06 Mn 0.02 ​O2 single crystal (referred to as SNCM-Bare).

[0028] B and Al coated LiNi 0.92 Co 0.06 Mn 0.02 O2 preparation: Ni 0.92 Co 0.06 Mn 0.02 (OH)2 precursor powder as raw material. Then, the precursor is mixed with LiOH H2O (5 mol% excess) and LiNO3 (LiOH H2O and LiNO3 molar ratio 1:1), LiOH H2O and LiNO3 molar amount is 1.05 times of the precursor, after mixing uniformly, pre-sintering at 500°C for 6h under oxygen environment, then heating to 750°C for 18h, then the obtained powder is mixed with 0.5mol% of B2O3 and Al2O3 (B2O3 and Al2O3 molar amount is 0.5% of the molar amount of the obtained powder), calcined at 820°C for 18h to obtain B and Al coated LiNi 0.92 Co 0.06 Mn 0.02 O2 (referred to as SNCM-BA).

[0029] Preparation of composite cathode: the prepared cathode above is mixed with Li3InCl6 (LIC) and vapor grown carbon fiber (VGCF) in a mortar according to the mass ratio of 70:28:2. In order to assemble a full solid-state battery, first, 80mg of LPSC and 40mg of LIC are placed in a 10mm polyether ether ketone (PEEK) cylinder in turn under the pressure of 300MPa for 3 minutes, the composite cathode material is added, and is pressed for 3 minutes under the pressure of 360MPa. Then, LiIn is applied to the other side of the battery, and is placed in a stainless steel plate under the pressure of about 20MPa.

[0030] Characterization

[0031] XRD analysis was performed on two samples, and the obtained XRD patterns were processed after refinement, showing that the lithium-nickel mixing ratio of the SNCM-Bare sample is 1.42%. The results show that there is a certain degree of mixing phenomenon between Ni 2+ / Li + After coating treatment, the Ni 2+ / Li + mixing ratio of the SNCM-BA sample decreases to 1.14%, which indicates that the coating process effectively improves the Ni 2+ / Li +The mixed arrangement helps improve the stability and cycle performance of the material. Furthermore, SEM images show that the prepared single-crystal ultra-high nickel cathode material particles have a particle size of approximately 3 μm and exhibit significant monodispersity with almost no grain boundaries. This phenomenon indicates that the material possesses high single-crystal structure characteristics, consistent with the preparation goals of single-crystal ultra-high nickel cathodes. To further confirm the coating status of B and Al elements in the SNCM-BA sample, TEM characterization was performed. Through TEM observation and elemental distribution analysis, such as... Figure 2 As shown, Ni and O elements are clearly and uniformly dispersed within the particles, indicating that these two elements form a stable crystal lattice structure in the material. In particular, the coated B and Al elements are only present on the particle surface, providing direct evidence regarding the coating layer. Further analysis of the TEM images clearly reveals the distribution of the mixed elements. In the elemental mapping, Ni appears blue, clearly concentrated in the central region of the particles, indicating that Ni is uniformly distributed throughout the particles and is the main component of the material. B is indicated in red, mainly distributed on the particle surface, indicating that B, as part of the coating layer, successfully covers the exterior of the Ni-O particles. Similarly, Al appears green, distributed on the surface of Ni, further verifying that Al and B work together in the coating layer to form an effective protective layer. This TEM analysis result shows that B and Al elements in the SNCM-BA sample not only successfully coat the particle surface but also form a uniform and stable coating layer, potentially improving the material's cycling stability and electrochemical performance.

[0032] To further pinpoint the distribution location of elements, a line scan of SNCM-BA was performed, such as... Figure 3 As shown, Al and B elements are present on the surface within 3 nm. Even in the bulk phase, trace amounts of Al are still present. The Ni element concentration gradually increases to the same level as the bulk phase within the surface (near 5 nm). To further accurately identify the surface states of B and Al, line-scan electron energy loss spectroscopy (EELS) analysis was performed on B and Al elements from the surface to the bulk phase. From near the surface to the interior of the bulk phase, the Al signal gradually weakens, and the B signal shows the same trend, with faster signal attenuation. This indicates that both B and Al are present on the surface, and that Al is doped into a portion of the bulk phase from the near surface. Due to the distribution of B, Al, and Ni elements on the surface of the SNCM-BA sample, this study further conducted a detailed morphological analysis of the near-surface region. Figure 4Figure a shows the HADDF-STEM results. Due to the high atomic numbers of transition metal elements (such as Ni), they appear as bright spots in the TEM image, while oxygen and lithium, with their lower atomic numbers, are not visible. In the bulk structure of SNCM-BA, a layered structure is clearly observed. In this structure, transition metal layers and lithium layers alternate, and the intermediate lithium layer does not show obvious bright spots, further confirming that Ni formation did not occur within the bulk phase. 2+ / Li + The phenomenon of mixed arrangement was observed. This result is consistent with the results of XRD refinement, indicating that the Ni in this sample... 2+ / Li + The mixing ratio (the ratio of I(003) / I(104)) is only 1.14%, meaning that the coating treatment effectively reduces Ni 2+ / Li + Further analysis of the near-surface region revealed TEM images showing the gradual emergence of bright spots within the layered structure, indicating that some transition metal atoms are distributed within the lithium layer. Figure 4 As shown in b, this phenomenon indicates that in the near-surface region of the sample, transition metal elements may have diffused into the lithium layer, leading to some changes in the local structure. However, in the outermost surface layer, the boundary between the lithium layer and the transition metal layer becomes indistinct, exhibiting a rock-salt phase structure, and the thickness of this surface layer is approximately 2-3 nm. This observation shows that the B and Al coating layers have a significant impact on the layered structure of the SNCM-BA sample surface. Specifically, the coating layers alter the atomic arrangement of the surface, gradually transforming from an initial disordered mix of cations to an ordered cation arrangement structure.

[0033] Electrochemical performance

[0034] To characterize the protective role of the cation-disordered interfacial layer during electrochemical processes, we assembled two samples, SNCM-BA and SNCM-Bare, into all-solid-state batteries. The voltage range was set to 2.7–4.5 V, and the current density was set to 1 C (1 C = 200 mAg). -1 ) Battery cycle performance and charge / discharge curves, etc. Figure 5 As shown in the figure. The experimental results show that the all-solid-state battery assembled with SNCM-BA exhibits a high specific capacity during the first discharge cycle, reaching 236.0 mAh g⁻¹. -1 Furthermore, its initial coulombic efficiency was 91%. In contrast, the all-solid-state battery assembled by SNCM-Bare only achieved 211.7 mAh g during its first discharge cycle. -1and the initial discharge specific capacity and coulombic efficiency of SNCM-BA were 175.6 mAh g-1 and 75%, respectively, which were obviously higher than those of SNCM-Bare. In terms of cycling performance, the capacity retention of SNCM-BA was still as high as 86% after 200 cycles at 1C current density, showing good cycling stability. However, the capacity retention of SNCM-Bare was only 43%, which was only half of that of SNCM-BA. This result indicates that the protective layer formed by the disordered structure on the surface of SNCM-BA effectively ensures the stability of the interface at high voltage of 4.5 V, thus achieving excellent high-voltage stability. This structural protective layer not only improves the initial discharge specific capacity and coulombic efficiency of the material, but also effectively prevents side reactions during the cycling process, ensuring a longer cycle life.

[0035] To further understand the reason why SNCM-BA is superior to SNCM-Bare in stability after surface engineering, we performed differential capacity (dQdV-1) analysis on the two samples. Both SNCM-BA and SNCM-Bare batteries experienced three distinct phase transition peaks. Specifically, as the voltage changes from low to high, they represent the transition from hexagonal to monoclinic phase (H1→M), the transition from monoclinic to hexagonal phase (M→H2), and the transition from hexagonal to hexagonal phase (H2→H3), respectively. Among them, the phase transition between H2 and H3 has a greater impact on the structural stability of the material. Since this phase transition usually leads to a significant anisotropic volume change, the material will be subjected to strong mechanical strain in the high-voltage (delithiation) state, which in turn affects its cycle performance and stability. Compared with SNCM-Bare, the peak position and intensity of the differential capacity curve of SNCM-BA change less after 200 cycles, indicating that its phase transition process gradually becomes irreversible, especially during the H2-H3 phase transition. The disordered structure protective layer of SNCM-BA effectively alleviates the volume change and strain of the material during the cycling process, reducing the damage of mechanical stress to the material structure, thereby improving the cycle stability of the material. This phenomenon shows that the disordered structure protective layer after surface engineering plays a key role in ensuring the reversibility of the phase transition process, effectively inhibiting the structural damage caused by the phase transition at high voltage, and providing an important guarantee for improving the long-term stability and electrochemical performance of the battery. Therefore, the excellent stability of SNCM-BA is mainly due to the role of its surface disordered structure protective layer, which not only slows down the strain caused by the phase transition process, but also enhances the structural stability of the material, making it maintain better cycle performance at high voltage.

[0036] To further verify the role of the surface interfacial disorder structure protective layer in the long-term cycling process, the assembled all-solid-state batteries were tested for long-term cycling at room temperature at 5C. The test results show that for the SNCM-BA all-solid-state battery, the initial discharge specific capacity is 146.2 mAhg -1 After 500 cycles, the discharge specific capacity is 137.4 mAhg -1 , and the capacity retention rate is 94%. This result shows that the SNCM-BA battery maintains a high capacity stability during long-term cycling, and the surface disorder structure protective layer effectively enhances the interfacial stability between the positive electrode and the solid-state electrolyte. In contrast, for the SNCM-Bare all-solid-state battery, the initial discharge specific capacity is 99.5 mAhg -1 , but after 10 cycles, the discharge specific capacity begins to rapidly decay. After 500 cycles, the discharge specific capacity decreases to 39.0 mAhg -1 , and the capacity retention rate is only 39%. This comparative result fully demonstrates that the disorder structure protective layer on the surface of the SNCM-BA battery significantly improves the interfacial stability of the battery and effectively suppresses the performance decay of the battery during long-term cycling. Both SNCM-Bare and SNCM-BA all-solid-state batteries exhibit gradually increasing discharge specific capacity at the initial cycle at 5C high current density, because the electrode material is gradually activated under high current density. Based on the SNCM-BA all-solid-state battery, the capacity retention rate is 86% after 200 cycles at 1C, and the capacity retention rate is 94% after 500 cycles at 5C.

[0037] Characterization of the protective layer of the surface interfacial reconstruction

[0038] SNCM-BA has this novel near-surface gradual transition from cationic disorder framework to typical layered structure, to characterize the protective effect of this novel interfacial layer, in-situ interfacial aging tests were carried out on SNCM-Bare and SNCM-BA, as shown in a, b of Figure 8 , the assembled all-solid-state battery was charged to 4.5V and kept constant voltage for 10h, and the impedance was measured every 30min in the constant voltage stage, so that the change of interfacial impedance can be observed in-situ in the constant voltage stage. As Figure 8As shown in figures c and d, for the SNCM-Bare all-solid-state battery, the impedance of the semicircle representing the interface impedance increases rapidly with the increase of the interface aging test time, from the initial 250Ω to 1500Ω. However, the impedance of the SNCM-BA all-solid-state battery only increases slightly, as can be seen from the corresponding magnified figure, only from 45Ω to 175Ω. To further quantify the protective effect of the interface layer, the impedance data is converted into a relaxation time distribution method for mathematical analysis of the EIS data. This method uses frequency-to-time domain conversion technology to decouple the Nyquist curve into a time-domain characteristic spectrum, such as... Figure 9 As shown in a and b, the horizontal axis is the time constant, 10 -3 ~10 -2 The S-peak represents the interfacial impedance between the cathode and the solid electrolyte. The graph shows that the SNCM-Bare cathode / solid electrolyte interfacial impedance increases rapidly, while the SNCM-BA impedance shows almost no change along the way. This is consistent with... Figure 8 The EIS curves in the data are consistent; 10 -1 ~10 0 s and 10 0 ~10 1 The S-peak represents the charge transfer impedance (Rct). The graph shows that the Rct color of SNCM-Bare rapidly changes from blue to red, indicating a sharp increase in Rct to 520Ω. However, the color change in SNCM-BA is only slight, indicating that Rct is relatively stable and small, ensuring good charge transfer at the interface. The overall interface aging test results show that, under constant voltage conditions, since the SNCM-Bare sample surface has no treatment, the high-valence Ni... 4+ It is prone to side reactions with the electrolyte, which can easily cause a rapid increase in the interface impedance and Rct of the cathode / solid electrolyte. However, the disordered structure on the surface of the SNCM-BA sample reduces the side reactions with the solid electrolyte, ensuring a good and stable interface.

[0039] In-situ mass spectrometry tests were performed on the assembled all-solid-state battery, such as... Figure 10 As shown. In the tests, the SNCM-Bare-based all-solid-state battery exhibited significant gas release. During charging, carbon dioxide (CO2) began to be released when the battery voltage reached 4.2V. This is mainly due to the release of products resulting from the decomposition reaction of lithium carbonate on the SNCM-Bare surface. Further increasing the voltage to 4.3V, the battery entered the H2 to H3 phase transition stage and began to release oxygen (O2). This phenomenon indicates that oxygen in the crystal lattice is deeply oxidized into gaseous oxygen, accompanied by Ni... 4+ The reduction of Ni 2+The formation of the new phase leads to a new phase transition of rock salt or spinel phase. In this process, the release of oxygen is closely related to the redox reaction of Ni and the detachment of lattice oxygen. However, for the SNCM-BA-based all-solid-state battery, no oxygen or carbon dioxide release was observed during the charging process. This indicates that the lattice oxygen of SNCM-BA is more stable than that of SNCM-Bare and is not easily over-oxidized to oxygen at high voltage during charging. This experimental result is consistent with the theoretical calculation, further verifying the higher stability of SNCM-BA at high voltage and long cycle. The Al-doped surface disordered structure of SNCM-BA effectively inhibits the release of oxygen, thereby reducing the formation of oxygen vacancies and the degradation of material structure.

Claims

1. A high-nickel cathode material for all-solid-state lithium batteries, characterized in that, It includes a high-nickel oxide bulk phase, which is a single crystal particle. The surface of the bulk phase also includes a coating layer containing Al and B. The coating layer has a thickness ranging from 1 to 10 nm. In addition, Al element is distributed in the 1-10 nm range near the surface of the bulk phase. The content of Al element gradually decreases from the near surface to the bulk phase. The coating layer changes from disordered mixing of cations to ordered arrangement of cations from the outside to the inside.

2. The all-solid-state lithium battery high-nickel cathode material according to claim 1, characterized in that, The particle size range of the single crystal particles is 1-20 μm.

3. The method for preparing the high-nickel cathode material for all-solid-state lithium batteries according to claim 1, characterized in that, Includes the following steps: A high-nickel precursor material was obtained, which was then ball-milled and mixed with a lithium source, followed by a first calcination. The pre-calcined material was then thoroughly mixed with B2O3 and Al2O3, and then calcined a second time to obtain the cathode material.

4. The method for preparing the high-nickel cathode material for all-solid-state lithium batteries according to claim 3, characterized in that, The high-nickel precursor material is Ni 0.92 Co 0.06 Mn 0.02 (OH)2.

5. The method for preparing the all-solid-state lithium battery high-nickel cathode material according to claim 3, characterized in that, The first calcination involves pre-calcining at 450-550℃ for 4-10 hours, followed by raising the temperature to 700-800℃ and holding for 15-25 hours; the second calcination involves holding at 800-850℃ for 15-25 hours.

6. The method for preparing the high-nickel cathode material for all-solid-state lithium batteries according to claim 3, characterized in that, The amounts of B2O3 and Al2O3 used are 1-10 mol% of the pre-fired material, respectively.

7. The method for preparing the high-nickel cathode material for all-solid-state lithium batteries according to claim 3, characterized in that, The lithium source is LiOHH2O and LiNO3, with a molar ratio ranging from 1:0.5 to 2.

8. The method for preparing the high-nickel cathode material for all-solid-state lithium batteries according to claim 7, characterized in that, The molar amount of lithium source is 1.5-2.5 times that of the precursor.

9. An all-solid-state lithium battery comprising a positive electrode made of the positive electrode material as described in claim 1.

10. A method to reduce Ni content in the cathode material of all-solid-state lithium batteries during charge-discharge cycles. 2+ / Li + The method for mixing ratios is characterized by, This refers to the formation of the aforementioned all-solid-state lithium battery high-nickel cathode material by coating the surface of a high-nickel oxide bulk phase with a coating layer containing Al and B.

Citation Information

Cited By

  • Solid-state battery system and preparation method thereof

    CN121416630A